2002
DOI: 10.1177/0888439002016004003
|View full text |Cite
|
Sign up to set email alerts
|

Motor Recovery and Cortical Reorganization after Constraint-Induced Movement Therapy in Stroke Patients: A Preliminary Study

Abstract: Constraint-induced movement therapy (CIMT) is a physical rehabilitation regime that has been previously shown to improve motor function in chronic hemiparetic stroke patients. However, the neural mechanisms supporting rehabilitation-induced motor recovery are poorly understood. The goal of this study was to assess motor cortical reorganization after CIMT using functional magnetic resonance imaging (fMRI). In a repeated-measures design, 4 incompletely recovered chronic stroke patients treated with CIMT underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(134 citation statements)
references
References 3 publications
6
122
0
6
Order By: Relevance
“…Voxel-based comparisons also showed significant changes in the anterior supplementary motor area contralateral to the motor deficit. This is the first study of structural changes in gray matter of cerebral cortex after constraint-based therapy, and the results complement previous data using functional methods (TMS mapping, PET, and fMRI) to document cortical changes following the procedure [Liepert et al, 2000;Schaechter et al, 2002;Wittenberg et al, 2003]. The results of the study highlight the importance of combining a behavioral intervention with the functional activity task and constraint of the better arm to produce functional improvement and structural change in the brain.…”
Section: Structural Neuroplasticity After Therapy For Hemiparesissupporting
confidence: 71%
“…Voxel-based comparisons also showed significant changes in the anterior supplementary motor area contralateral to the motor deficit. This is the first study of structural changes in gray matter of cerebral cortex after constraint-based therapy, and the results complement previous data using functional methods (TMS mapping, PET, and fMRI) to document cortical changes following the procedure [Liepert et al, 2000;Schaechter et al, 2002;Wittenberg et al, 2003]. The results of the study highlight the importance of combining a behavioral intervention with the functional activity task and constraint of the better arm to produce functional improvement and structural change in the brain.…”
Section: Structural Neuroplasticity After Therapy For Hemiparesissupporting
confidence: 71%
“…The increase in the healthy hemisphere may also suggest bilateral participation of primary motor cortices in voluntary movement execution after the therapy. Increased ipsilateral motor cortex involvement in movement execution has been reported after CIMT in stroke patients (Schaechter et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5][6] One limitation of training protocols is that patients with more profound weakness are unable to carry out the motor routines required. The finding that passively elicited motions lead to activation and cortical reorganization in brain regions common to those activated with performance of voluntary movements suggested that it could also elicit improvements in motor function.…”
Section: Role Of Volition In Motor Learningmentioning
confidence: 99%